Macbeth [videorecording (DVD)] : the Royal Shakespeare Company production - Shakespeare, William, 1564-1616; Casson, Philip; McKellen, Ian; Dench, Judi, 1934-; Brown, John, 1934 July 1-; Dury, Susan; Hicks, Greg, 1953 May 27-; McDiarmid, Ian; Peck, Bob, 1945-1999; Rees, Roger, 1944-2015; Woodvine, John, 1929- (Thames Shakespeare collection, 2004)
When a trio of witches prophesy Macbeth's ascension to the throne, Lady Macbeth pushes her husband into a murderous spree. But once crowned king of Scotland, Macbeth sees ghastly visions, fueled by guilt and a new prophecy, that ensure his ultimate downfall.